Enhancing High School Students’ Sentence Structure Skills by Integrating Artificial Intelligence (AI) Application in English Learning Process: English - Dwi Putri Ramadani; Imelda Darmayanti Manurung (Journal of English Development, 2024)
Abstract This study aims to investigate the significance of sentence structure in the acquisition of English language skills. It also seeks to identify the difficulties encountered by English learners in understanding sentence structure and propose effective solutions to assist them in overcoming these problems. The study employs a pre-experimental research design with a quantitative methodology. The research sample consisted of 30 respondents or students of English as a second language, who were separated into three separate classes. The AI intervention group demonstrated significantly higher levels of engagement (behavioural, emotional, and cognitive) than students in the no-AI equipment (NEAI) group. The results of this study suggest that AI may help students be more proficient writers